Conquering stroke - Greene, Valerie (Wiley, 2008)
Includes bibliographical references (p. 249-250) and index.; A stroke survivor and American Heart Association spokesperson shares her story and cutting-edge medical advice on stroke prevention and treatment. Stroke is the third leading cause of death in the United States today and the leading cause of adul.